2015
DOI: 10.35680/2372-0247.1039
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients’ experiences of error and consequences during diagnosis and treatment

Abstract: The study objective was to investigate patient experienced error during diagnosis and treatment of cancer. included a nationwide patient survey on quality and safety in Danish cancer care. Responses regarding patient experienced error were separately analyzed, quan using systematic text analysis. Study participants included registered between May 1st and August 31st 2010 care received by general practitioners, specialist 10-25% of patients experienced error during diagnosis or treat consequences. Unexpected su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Another significant area of supportive needs identified in the period leading up to diagnosis relates to the impact of misdiagnosis and lack of person-centric responses to patients’ requests for symptom appraisal. Just over a quarter of the personal accounts in our study described experiences of a missed clinical diagnosis, reflecting the quantitative evidence from Blum et al (2007) reporting between 20% and 33% of clinicians in first consultations giving a misdiagnosis, and findings of Lipczak, Dørflinger, Enevoldsen, Vinter, & Knudsen (2015) that up to 25% of reviewed cancer patients experienced diagnostic errors.…”
Section: Discussionmentioning
confidence: 53%
“…Another significant area of supportive needs identified in the period leading up to diagnosis relates to the impact of misdiagnosis and lack of person-centric responses to patients’ requests for symptom appraisal. Just over a quarter of the personal accounts in our study described experiences of a missed clinical diagnosis, reflecting the quantitative evidence from Blum et al (2007) reporting between 20% and 33% of clinicians in first consultations giving a misdiagnosis, and findings of Lipczak, Dørflinger, Enevoldsen, Vinter, & Knudsen (2015) that up to 25% of reviewed cancer patients experienced diagnostic errors.…”
Section: Discussionmentioning
confidence: 53%
“…The current SR highlights a lack of data relating to the patient health consequences of chemotherapy accuracy and dose errors in studies investigating compounding technologies. However, research suggests that errors during the treatment of cancer can potentially lead to physical, psychological and social consequences for the patient 41…”
Section: Discussionmentioning
confidence: 99%
“…In two recent Australian studies, 26% of 166 haematology patients reported an unexpected adverse event during their care (Bryant et al, 2017); while 13% of 1136 medical oncology outpatients reported experiencing a health care error (Carey et al, 2019). Among a sample of 4346 Danish cancer patients, 25% experienced an error during their hospital treatment and 61% of these patients experienced negative outcomes (Lipczak, Dørflinger, Enevoldsen, Vinter, & Knudsen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Health care errors can result in pain, suffering, loss of independence, loss of productivity for patients and families and even death (Blignaut, Coetzee, Klopper, & Ellis, 2017;Lipczak et al, 2015). Patients and families can also experience physical, emotional and financial trauma following a health care error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation